Optimalisasi Teknologi dan Pembekalan Aspek Hukum Hak Kekayaan Intelektual (HKI) pada UMKM di Masa Pandemi - Yordan Gunawan; Mohammad Bima Aoron Hafiz (Universitas Muhammadiyah Magelang, 2022)
The main focus of this community service is to change the mindset of people who are UMKM entrepreneurs to improve the economy so that partners can understand and take advantage of digital marketing and intellectual property rights as part of business systems and strategies. In addition, partners can carry out commercialization by carrying out correct and efficient intellectual property rights registration procedures, so that the business activities carried out can improve people's lives while protecting their copyrights. This community service method uses an active and interactive participation-based approach by providing counseling, training, and sustainability programs. This pattern places partners more as active participants in an atmosphere of non-formal or attractive activities so that they are able to generate knowledge absorption that provides new innovations for the community, increases productivity during the pandemic, and provides a briefing to partners on the legal aspects of Intellectual Property Rights in Indonesia.